Anhedonic-like behavior and BDNF dysregulation following a single injection of cocaine during adolescence. (15th September 2020) - Caffino, Lucia; Mottarlini, Francesca; Mingardi, Jessica; Zita, Gianmaria; Barbon, Alessandro; Fumagalli, Fabio
Abstract: We have previously demonstrated that a single exposure to cocaine during adolescence causes several behavioural and neurobiological changes, highlighting the unique vulnerability of this period of life. The purpose of our work was to investigate whether a single exposure to cocaine during brain development is sufficient to shape a negative emotional state in adolescent rats. A single injection of cocaine during adolescence followed by measurement of sucrose consumption, a measure of anhedonia, identifies two separate groups of rats, i.e. anhedonic (AN) and non anhedonic (NON-AN) rats. AN rats show reduced ability to synthesize, traffic and translate the neurotrophin BDNF at synaptic level, reduced activation of hippocampal BDNF signaling, reduced BDNF plasma levels and a steep rise of corticosterone secretion. Conversely, NON-AN rats exhibit reduced trafficking of BDNF while up-regulating hippocampal BDNF synthesis and stabilizing its downstream signaling with no changes of BDNF and corticosterone plasma levels. Adult rats exposed to cocaine showed no signs of anhedonia, an increase of BDNF both in hippocampus and plasma and decreased levels of corticosterone. In conclusion, our findings reveal a complex central and peripheral dysregulation of BDNF-related mechanisms that instead are preserved in NON-AN rats, suggesting that BDNF modulation dictates behavioural vulnerability vs. resiliency to cocaine-induced anhedonia, a profile uniquely restricted to adolescent rats. Graphical abstract: Image 1 Highlights: A single injection of cocaine during adolescence is sufficient to cause anhedonia. Anhedonic rats show central and peripheral dysregulation of BDNF-related mechanisms. Resilient rats exhibit increased BDNF hippocampal levels with no peripheral changes. Adult rats exposed to cocaine do not develop anhedonia upregulating the BDNF system.